Conditional effects of open-street closed-circuit television (CCTV) on crime: A case from Korea. (June 2018) - Jang, Yongseol; Kim, Dohyeong; Park, Junhwi; Kim, Dowoo
Abstract: Prior studies reported mixed findings concerning the effects of Closed-Circuit Television (CCTV) on crime reduction. By utilizing the multi-contextual criminal opportunity theory, this study aims to determine the conditional effects of open-street CCTV surveillance system on crime across socioeconomic and physical environmental factors. Using the data from one district in Seoul, Korea, we ran a series of Poisson regression models with interaction terms allowed for articulating the conditional effects of CCTVs on crime. In line with studies in Western countries, CCTVs in Korea were significantly associated with levels of property crime and the areas with larger surveillance zones had lower property crime levels. Also, there was a conditional crime reduction effect of CCTVs on assaults, depending on the areal density of alcohol outlets. The conditional effect of CCTVs suggests some neighborhood characteristics optimize the deployment of CCTVs, which guide more effective implementation of CCTV systems for crime control and prevention.